Green electrode processing using a seaweed-derived mesoporous carbon additive and binder for LiMn2O4 and LiNi1/3Mn1/3Co1/3O2 lithium ion battery electrodes. Issue 2 (5th December 2018) - Kim, Sanghoon; De bruyn, Mario; Louvain, Nicolas; Alauzun, Johan G.; Brun, Nicolas; Macquarrie, Duncan J.; Boury, Bruno; Stievano, Lorenzo; Mutin, P. Hubert; Monconduit, Laure
Abstract : Eco-friendly lithium ion battery electrode processing was elaborated using seaweed-derivatives. Abstract : Eco-friendly and cheap lithium ion battery electrode processing using a seaweed-derived mesoporous carbon additive (Starbon® A800) and binder (sodium alginate) was elaborated for LiMn2 O4 (LMO) and LiNi1/3 Mn1/3 Co1/3 O2 (NMC) lithium ion batteries. Compared to electrodes made using conventional formulations ( i.e. Super P/PVDF) the 'green' electrodes can provide significantly 'upgraded' reversible capacity, almost reaching their theoretical capacity at low C-rate, likely due to good accessibility of lithium ions via the mesopores of the carbon additive. In addition, a synergistic effect was observed for a binary carbon additive system composed of Starbon® A800 with conventional carbon black (Super P), improving both the initial capacity and the rate capability of LMO and NMC electrodes.